PBPK Modeling on Organs-on-Chips: An Overview of Recent Advancements - Yang, Yi; Chen, Yin; Wang, Liang; Xu, Shihui; Fang, Guoqing; Guo, Xilin; Chen, Zaozao; Gu, Zhongze (Frontiers in Bioengineering and Biotechnology, 2022)
Organ-on-a-chip is a new and promising technology, which aims to improve the efficiency of drug development and realize personalized medicine by simulating in vivo environment in vitro. Physiologically based pharmacokinetic (PBPK) modeling is believed to have the advantage of better reflecting the absorption, distribution, metabolism and excretion process of drugs in vivo than traditional compartmental or non-compartmental pharmacokinetic models. The combination of PBPK modeling and organ-on-a-chip is believed to provide a strong new tool for new drug development and have the potential to re-place animal testing. This article provides the recent development of organ-on-a-chip technology and PBPK modeling including model construction, parameter estimation and validation strategies. Application of PBPK modeling on OoC has been emphasized, and considerable progress has been made. PBPK modeling on OoC would become an essential part of new drug development, personalized medicine and other fields.